Development of indirect IgG ELISA for detection of leptospiral infection in cattle using Malaysian local isolate Leptospira kmetyi serovar malaysia strain Bejo-Iso9 - Abdul Rahman, Mohammad Sabri; Bejo, Siti Khairani; Zakaria, Zunita; Hassan, Latiffah (Veterinary Association Malaysia, 2017)
Cattle is one of an important maintenance hosts involved in the transmission of leptospirosis. Serological method is always implemented to detect current or past leptospiral infection in cattle. The results can be obtained immediately compared to isolation method which need more longer time. An in-house IgG enzyme-linked immunosorbent assay (ELISA) using heat-killed whole cells of local isolate Leptospira kmetyi serovar malaysia strain Bejo-Iso9 (ELISA-Bejo-Iso9) was developed in this study. The perfomance of ELISA-Bejo-Iso9 was compared with in-house IgGELISA using reference strain 117123 (hardjo bovis) antigen (ELISA-117123) and CUSABIO® commercial ELISA. It was found that, the performance of ELISA-Bejo-Iso9 was promising to compete with commercial ELISA. The specificity and sensitivity was 98.75% and 53.75%, respectively. The sensitivity of ELISA-Bejo-Iso9 was lower than commercial ELISA. However, the specificity of ELISA-Bejo-Iso9 was higher than commercial ELISA. Due to economically and availability factors, this finding suggested that the ELISA-Bejo-Iso9 can be used as an alternatif method for serological diagnosis of leptospirosis in cattle.